PERAN PENDIDIKAN DALAM PENGEMBANGAN LITERASI DIGITAL - Kamaliah, Lutfiyatul; Rosidah, Cholifatur; Talenta, Ikmal Diva; Ariestiyani, Ema; Utami, Agusti Restu (STKIP PGRI Situbondo, 2025)
Abstrak: The Industrial Revolution era 4.0 is characterized by low-speed technological advances driven by artificial intelligence, or AI (Artificial Intelligence). Books are usually considered the main teaching medium used in the field of education. Reading is one way to gain self-awareness and understand existing texts. However, we must admit that the literacy level in Indonesia is currently still quite low. The current situation in Indonesia is a serious matter that we must discuss together. The low interest in reading is backward in quality and the quality of education in Indonesia tends to decline. The purpose of this study is to understand the role of education in the development of digital literacy. The research design used in this study is a qualitative approach using a descriptive method. The findings of this study show that students are quite proficient in using digital media, such as reading Wattpad, watching web cartoons, or completing assignments. Thus, this research was made, so that in the future digital literacy will be able to provide accurate knowledge, insights, and information for readers.